A CHECKLIST OF THE FAMILY LAUXANIIDAE (DIPTERA, LAUXANIOIDEA) IN VIETNAM - Hyun Suk Lee (Tạp chí Khoa học Đại học Đà Lạt)
I reviewed the lauxaniid literatures as much as possible, and listed any lauxaniid species with collecting records in Vietnam. Vietnamese lauxaniid flies belong to two subfamilies. In this paper, I provide a taxonomic checklist of 60 nominal species under the subfamily Homoneurinae. However, this checklist is based on information of diverse literatures, not confirmation of identifications with each species. I will provide other checklist of lauxaniid species under the subfamily Lauxaniinae as soon as possible. A more comprehensive research is needed to confirm identifications of previously recorded lauxaniid species in Vietnam.